A Study of the Impact of the Dissemination of Ancient Chinese Primer Classic in the United States - Rong, Jianting (Cultural and religious studies, 2023)
Carrying the roots of Chinese civilization to its origins, the Chinese Primer classic has received considerable attention in the international community’s cultural diffusion. The spread of the Chinese Primer class studies in the United States, aided by missionaries such as E. C. Bridgeman, Samuel Wells Williams, and William Alexander Parsons Martin, sinologists such as Witter Bynner and David Hinton, has been characterized by unidirectionality, permeability, and pluralism.